INTEGRASI ASPEK RISIKO DALAM MODEL UNIFIED THEORY OF ACCEPTANCE AND USAGE OF TECHNOLOGY UNTUK MENGANALISIS PENERIMAAN TEKNOLOGI GO-RIDE - Alfan Amrullah; Anjar Priyono (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract: This research aims to analyse the acceptance of Go-Ride, motorbike taxibooking application, using Unified Theory of Acceptance and Usage of Technology(UTAUT) model. The uniqueness of this study is that it integrates risk into the UTAUTmodel. Four variables were used as independent variables including peformanceexpectancy, effort expectancy, social influence and facilitating condition. Meanwhile,three variables are used as moderating variables: gender, age and experience.University students were selected as respondent because young age people tends to bemore risk takers in comparison to the old one. According 151 data samples collectedfrom university students, the results demonstrated that acceptance of Go-Ridetechnology influenced by four factors: performance expectancy, effort expectancy,social influence and behavioral intention On the otherhand, performance risk, financialrisk, time risk and facilitating condition do not support to the acceptance and usage ofGo-Ride technolology.